Analisis pelatihan kerja untuk meningkatkan kinerja karyawan pada CV. Gema Abhipraya (Rasi Coffee) - Nurhaliza, Diva; Alamsyah, Agus (Politeknik Negeri Ambon, 2025)
The company must design each employee to have appropriate abilities in the commercial field, especially to improve employee performance through job training. Job training has an important role in improving employee performance because the lack of job training will have an impact on employee performance that is not optimal, such as in the quality of the products presented. This study aims to determine the role and influence of job training on employee performance at Rasi Coffee. In addition, to determine employee perceptions of the job training provided. The results of the study show that Rasi Coffee has implemented a job training strategy based on on the job training rotation and experimental methods, to improve employee performance. The research method used is a descriptive qualitative approach with a total of 7 respondents. The research instruments used are interviews, observation, and documentation. The results of the analysis show an increase in employee job training by 17% from 2022 to 2024. This means that job training has a positive impact on the development of employee performance skills.